2010
DOI: 10.1139/z09-129
|View full text |Cite
|
Sign up to set email alerts
|

What is the taxonomic identity of Minnesota wolves?

Abstract: The taxonomic identity of the historical and current wolf (Canis lupus L., 1758 or Canis lycaon Schreber, 1775 or their hybrids) population in Minnesota (MN) and the Great Lakes region has been, and continues to be, controversial. So too does its legal status under the U.S. Endangered Species Act. This review summarizes the morphological and genetic information about that population and concludes that historically the MN population consisted of a gray wolf (C. lupus) in the west and an eastern type (Canis lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Morphometric analyses by Skeel and Carbyn (1977) provide general support for a comparable distribution of larger and smaller wolves in central Canada. Autosomal microsatellite data (Carmichael et al 2007(Carmichael et al , 2008) distinguish C. 1. nubilus from C. 1. occidentalis in the northeastern portion of its range, and both microsatellite and mtDNA data (Weckworth et al 2005(Weckworth et al , 2010Munoz-Fuentes et al 2009, 2010 Nowak (1995Nowak ( , 2003, at least in the areas covered by those studies.…”
Section: Fuscus (British Columbia Except For Vancouvermentioning
confidence: 92%
See 2 more Smart Citations
“…Morphometric analyses by Skeel and Carbyn (1977) provide general support for a comparable distribution of larger and smaller wolves in central Canada. Autosomal microsatellite data (Carmichael et al 2007(Carmichael et al , 2008) distinguish C. 1. nubilus from C. 1. occidentalis in the northeastern portion of its range, and both microsatellite and mtDNA data (Weckworth et al 2005(Weckworth et al , 2010Munoz-Fuentes et al 2009, 2010 Nowak (1995Nowak ( , 2003, at least in the areas covered by those studies.…”
Section: Fuscus (British Columbia Except For Vancouvermentioning
confidence: 92%
“…Skeel and Carbyn's (1977, (Nowak 1995(Nowak , 2002(Nowak , 2009), Nowak recognizes the eastern wolf as a subspecies of C. lupus and restricts its range to southern portions of Ontario and Quebec, while attributing Minnesota wolves to C. 1. nubilus. His Minnesota samples, however, were taken after 1960 (Nowak 1995(Nowak 2002, during a period of likely increased movement into Minnesota of C. 1. nubilus from the west and north (Mech and Frenzel 1971;Mech and Paul 2008;Mech 2010;Mech et al 2011). Nowak's data for Minnesota likely reflect this substantial and recent contribution of C. 1. nubilus to Minnesota wolves.…”
Section: Species Limits Of Canis Lupus Relative To Eastern Wolfmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid was originally called the Tweed Wolf (Kolenosky and Standfield 1975;Wilson et al 2009). Recent research indicates that the medium-sized Eastern Wolf (Rutledge et al 2010b;Chambers et al 2012;Rutledge et al 2012aRutledge et al , 2012b was probably the original species native to northeastern North america, with potential influence from Gray Wolves (Canis lupus) (or their hybrids) from the north (Kyle et al 2008;Wilson et al 2009;Fain et al 2010;Mech 2010;Chambers et al 2012;Wheeldon and Patterson 2012), but see the discussion in vonholdt et al (2011) for an alternate interpretation. In addition, a new theory (vonholdt et al 2011) (also see Wheeldon and Patterson 2012) holds that domestic dogs (C. lupus familiaris) contributed ~9% to the genetic composition of the northeastern Coyote (previous genetic studies detected no dog influence (Way et al 2010) or insignificant amounts (Kays et al 2010)).…”
mentioning
confidence: 99%
“…Most of the recent reviews on eastern North american Canis have focused on Eastern Wolves and have concluded that the Eastern Wolf is a distinct species (e.g., Fain et al 2010;Mech 2010Mech , 2011Chambers et al 2012;Rutledge et al 2012a). however, there has also been an abundance of recent papers on Coyote genetics in eastern North america (e.g., Chambers 2010; Kays et al 2010;Way et al 2010;Wheeldon et al 2010a;Bozarth et al 2011), and I therefore attempt to synthesize these papers.…”
mentioning
confidence: 99%